Neoliberalism, the Knowledge Economy, and the Learner: Challenging the Inevitability of the Commodified Self as an Outcome of Education. (23rd April 2013) - Patrick, Fiona
Abstract : Neoliberalism is now a globalised agenda that underpins educational strategy and policy in many nations. The evolution of the concept of the knowledge economy and of the knowledge worker has been allied to the rise of neoliberalism as an end with respect to educational processes. This review article considers the ways in which constructs of the knowledge economy within a neoliberal agenda have given rise to specific discourses and conceptualisations of educational outcomes and aims. In particular, the value of knowledge and learning within neoliberal constructions of education will be discussed. The positioning within these constructions of the learner as a reification of economic capital will also be explored. This paper argues for a reconsideration of the purposes of education if the commodified self is to be resisted.